Methyl 3,4-dihydroxybenzoate inhibits RANKL-induced osteoclastogenesis via Nrf2 signaling in vitro and suppresses LPS-induced osteolysis and ovariectomy-induced osteoporosis in vivo - Huang Zhaobo; Jiang Zenghui; Zheng Zeyu; Zhang Xuyang; Wei Xiaoan; Chen Jian; Zhao Fengdong (Acta Biochimica et Biophysica Sinica, 2022)
Osteoporosis deteriorates bone mass and biomechanical strength and is life-threatening to the elderly. In this study, we show that methyl 3,4-dihydroxybenzoate (MDHB), an antioxidant small-molecule compound extracted from natural plants, inhibits receptor activator of nuclear factor-κB (NF-κB) ligand (RANKL)-induced osteoclastogenesis in vitro. Furthermore, MDHB attenuates the activation of mitogen-activated protein kinase (MAPK) and NF-κB pathways by reducing the levels of reactive oxygen species (ROS), which leads to downregulated protein expression of c-Fos and nuclear factor of activated T cells c1 (NFATc1). We also confirm that MDHB upregulates the protein expression of nuclear factor-erythroid 2-related factor 2 (Nrf2), an important transcription factor involved in ROS regulation, by inhibiting the ubiquitination-mediated proteasomal degradation of Nrf2. Next, animal experiments show that MDHB has an effective therapeutic effect on lipopolysaccharide (LPS)- and ovariectomized (OVX)-induced bone loss in mice. Our study demonstrates that MDHB can upregulate Nrf2 and suppress excessive osteoclast activity in mice to treat osteoporosis.